Optimal Placement and Sizing of Capacitor in Radial Distribution Network Using Fuzzy and BFOA - Kishore, Chandan (EIED, 2016)
This dissertation represents an approach for the ideal placing and sizing of capacitors in radial distribution networks (RDNs) using the application of fuzzy and Bacterial Foraging Optimization Algorithm (BFOA). In the early day’s reduction of losses in power distribution networks had been a greater challenge. Compensating the power of the system has become the major tool to improve the stability of the system. The reactive power compensation of the power distribution system is significantly improved by capacitor placement which is one of the most impressive techniques that are used to reduce losses. The capacitor allocation for distribution system problem involves determining the ideal place and also the perfect size of the capacitor. In this work, load flow is performed at first to compute the losses and voltages at different nodes without compensation. In the proposed technique the combined approach of LSF (Loss sensitivity factor) and VSI (Voltage stability index) are used to determine the optimal placement of capacitor banks. The optimal size of the capacitor banks has been determined by Bacterial Foraging Optimization Algorithm (BFOA). To justify the objective of the proposed method after installing the capacitor, the load flow is performed again to get the system losses and node voltages. The suggested system is tried out on standard IEEE 33-node, 69-node and 141-node radial distribution systems and compared with other existing methods.
Keywords: Radial distribution network; Loss Sensitivity Factor; Fuzzy Logic; Capacitor; BFOA